Erratum to: A note on rank 5/2 Liouville irregular block, Painlevé I and the H 0 $$ {\mathcal{H}}_0 $$ Argyres-Douglas theory - Hasmik Poghosyan; Rubik Poghossian (Journal of High Energy Physics)
A correction to this paper has been published: https://doi.org/10.1007/JHEP11(2023)198